2010
DOI: 10.1590/s0102-67202010000200012
|View full text |Cite
|
Sign up to set email alerts
|

Escolha do material da tela para disposição intra-peritoneal na correção cirúrgica de defeitos herniários da parede abdominal

Abstract: INTRODUÇÃO: O uso de telas para a correção cirúrgica de defeito herniários da parede abdominal contribuiu para a acentuada redução dos índices de recidiva das hérnias. Contudo, o seu uso intra-abdominal cursa com a formação de aderências e diversas complicações, dentre elas a obstrução intestinal. MÉTODO: Foram selecionados, nos bancos de dados PubMed e Medline, 27 artigos científicos atualizados e com informações relevantes à respeito das propriedades mais importantes das telas (material, diâmetro dos poros, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The use of surgical meshes for closure of the abdominal cavity has improved hernia recurrence rates because the mesh provides higher tensile strength to the abdominal wall and decreases the recurrence of postoperative hernia 6,9,[10][11][12][13][14]21 . However, surgical meshes have brought with them several complications, such as fistulas and adhesions, especially with intraperitoneal use 2,7,14,[16][17][18][19] .…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of surgical meshes for closure of the abdominal cavity has improved hernia recurrence rates because the mesh provides higher tensile strength to the abdominal wall and decreases the recurrence of postoperative hernia 6,9,[10][11][12][13][14]21 . However, surgical meshes have brought with them several complications, such as fistulas and adhesions, especially with intraperitoneal use 2,7,14,[16][17][18][19] .…”
Section: ■ Discussionmentioning
confidence: 99%
“…With the advent of laparoscopic surgery and the placement of intraperitoneal meshes, major adhesion formation was highlighted 2,7,[14][15][16][17][18][19] . The composite meshes -which have the surface facing the viscera made of absorbable and microporous material and the surface facing the muscles made of synthetic macroporous material -are the ones with the best results 20,21 . This composition would be ideal since the biological component of the inner surface would avoid contact between the macroporous part and the abdominal viscera, reducing rates of complications such as adhesions 12 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several studies have evaluated the use of intraperitoneal mesh [5][6][7][8][9] . Baroncelli et al 7 comparing the healing process between the Parietex ® and Surgisis ® meshes in the correction of abdominal wall defects in rabbits, observed that the Parietex ® and Surgisis ® were effective in correcting the defects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, polypropylene mesh remains soft and flexible and it is not subject to weakening by the action of enzymes, providing a suitable frame for the deposition of collagen and embedding adjacent tissues (BELLON et al, 1998). However, according to Araújo et al (2010), the inflammatory process is more intense in animals that have received polypropylene implants when compared to the receptors that have attached biological biomaterials. There is also a higher possibility of adhesion formation.…”
Section: Discussionmentioning
confidence: 99%